Radiographic Features of Facial Cosmetic Material: Report of Two Cases - Noura A. Alsufyani; Mohammed A. Alsufyani (Hindawi Limited, 2021)
Recently, the use of noninvasive facial cosmetic procedures has been widely disseminated. In the face, cosmetic fillers, threads, and implants are used to reduce or delay the effects of aging or adjust facial defects caused by trauma or disease. The dentist or dental specialist may encounter these materials in the radiographic images of their patients. There are few reports in the dental literature describing the radiographic appearance of some materials along with the diseases they mimic. As the procedures and materials advance and evolve, dentists and dental specialists must be aware of their radiographic appearance to avoid errors in diagnosis. This is a report of two cases that include panoramic radiography and CBCT scan. Among these cases, there is an unusual appearance of a cosmetic filler due to a subperiosteal injection method. Moreover, it will discuss common types of cosmetic materials used in the face and their imaginological appearance. This is the key to dentists and dental specialists due to increasing use of facial cosmetic materials and a parallel increase in the use of cone beam CT and chances to encounter such findings.